FACTORS OF SEXUALLY TRANSMITTED INFECTION SYMPTOMS AMONG WOMEN IN NORTH SUMATERA, INDONESIA: A CROSS-SECTIONAL STUDY - Salmaddiina, Aulia; Hanifah, Almira Nur (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: Sexually transmitted infections (STIs) are illnesses that spread from person to person through sexual activity. In Indonesia, STI cases increased between 2016 and 2017. One of the high cases reported in North Sumatra with 1,183 STIs cases which ranked seventh in Indonesia and second on Sumatera Island. Purpose: This study aimed to analyze the risk factors related to women with STIs symptoms in North Sumatra. Methods: A cross-sectional study was conducted using the 2017 Indonesian Demographic Health Survey data which included a total sample of 2,440 women aged 15-49 years domicile in North Sumatera. Then, using IBM SPSS 25 to perform a multivariate analysis utilizing logistic regression. Results: This study showed that women with a genital ulcer were associated with living in rural areas (OR: 2.68, 95% CI: 1.67-4.31), poor economic status (OR: 1.47, 95% CI: 0.94-2.29), and the spouse having other sex partners (OR: 0.54, 95% CI: 0.31-0.94). Moreover, women who lived in rural areas (OR: 1.74, 95% CI: 1.38-2.20), had poor economic status (OR: 1.33, 95% CI: 1.05-1.68), and their spouse has STIs (OR: 0.51, 95% CI: 0.39-0.66) were associated with vaginal discharge. Conclusion: Findings indicated that STIs symptoms were higher among women who lived in rural areas with poor economic status and had negative attitudes toward negotiating safe sex with partners. It is advised that intervention programs focus more on conducting mass STIs testing and safe sex campaign in rural areas.